Coal Mine Seismicity And Bumps: Historical Case Studies And Current Field Activity - John L. Ellenberger (International Conference on Ground Control in Mining, 2000)
The National Institute for Occupational Safety and Health (NIOSH) has continued the research role of the former U.S. Bureau of Mines to develop techniques that will reduce the hazards in the mining work place associated with coal bumps. Current research focuses on both analyzing historical seismic data from bump-prone operations and utilizing a mine-wide seismic network to investigate the exact strata failure mechanics associated with bump-prone geology. The anticipated outcome of this research will be reduced bump incidences through advanced engineering concepts and designs which implement the new understanding of strata behavior. The analysis of the historic seismic data consists of correlating observed mining seismicity with the geologic and geometric parameters at the sites. The primary seismic parameters are the timing, location and magnitude of a recorded seismic event. These parameters are correlated with such mining parameters as: the overburden, the size of the immediate gob, the size of the district gob area, etc. This detailed analysis of historical seismic data has provided an informative quantifiable relationship between many of the specific mining parameters and the induced seismicity. The second aspect of the coal bump research is the instrumentation of an appropriate field site to determine the main roof, floor, and gob behavior associated with hump behavior. The chosen field site is a deep-cover longwall mine with competent geology in a historically bump-prone area. The primary field instrumentation is a three-dimensional, full-waveform, seismic array with both surface and underground sensors surrounding an active multi-panel district. The purpose of this seismic array is to determine the timing, the exact location, and the mechanism (tensile fracture, bedding plane slip. etc.) of the failure of the strata surrounding the active and multi¬panel gobs. The preliminary results presented in this paper help to define the strata failure areas around the longwall panel.